Microwave Assisted Synthesis of Pyrazolo[1,5-a]pyrimidine, Triazolo[1,5-a]pyrimidine, Pyrimido[1,2-a]benzimdazole, Triazolo[5,1-c][1,2,4]triazine and Imidazo[2,1-c][1,2,4]triazine - Fahim, Asmaa; Farag, Ahmad; Shaaban, Mohamed; Ragab, Eman (Current Microwave Chemistry, 2018)
Background: This paper describes the synthesis of novel fused heterocycles, from the reaction 2-cyano-N-cyclohexyl-3-acrylamide derivatives 5a-f with nitrogen nucleophilic reagents, which carried out under microwave irradiation. Reactivity of 3 towards diazonium amines salts to afford hydrazones undergo cyclization to give amino pyrazole and the fused heterocyclic compounds incorporating cyclohexyl moiety. The synthesized compounds excellently utilized microwave irradiation in short time and high yield. Methods: Synthesis of Fused heterocycles derivatives from 2-cyano-N-cyclohexyl acetamide utilizing Microwave irradaition. Results: Regioselective facile synthesis of innovative heterocycles from the reaction of 2-cyano-Ncyclohexyl acetamide (3) with appropriate aldehydes to afford the corresponding acrylamide derivatives 5a-f under microwave irradiation. Acrylamides 5 reacts with hydrazine derivatives affording the corresponding pyrazole derivatives 7a and 7b, furthermore the treatment of acrylamides 5 with 2-amino benzimidazole, amino pyrazole, and aminotriazole derivatives to gives corresponding pyrimido[1,2-a]benzimdazole 10, pyrazolo[1,5-a]pyrimidine 12 and triazolo[1,5-a]pyrimidine 14; respectively in good yield. Reactivity of 3 towards diazonium amines salts afforded hydrazones derivatives, which undergo cyclization to give the corresponding derivatives 19a and the fused pyrazolo[5,1-c][1,2,4]triazine 22, triazolo[5,1-c][1,2,4]triazine 24 and imidazo[2,1-c][1,2,4]triazine 28 incorporating cyclohexyl moiety. Conculsion: In this investigation, we have synthesized innovative pyrimido[1,2-a]benzimdazole, and triazolo[1,5-a]pyrimidine, pyrazolo[1,5-a]pyrimidine, 2-amino benzimidazole, amino pyrazole, aminotriazole, fused pyrazolo[5,1-c][1,2,4]triazine, triazolo[5,1-c][1,2,4]triazine and imidazo[2,1- c][1,2,4]triazine derivatives incorporating cyclohexyl moiety utilizing microwave irradiation. The compounds were obtained under microwave reaction in excellent yield in a short reaction time.
Keywords: fused heterocycles